Kidney segmentation in ultrasound, magnetic resonance and computed tomography images: A systematic review. (April 2018) - Torres, Helena R.; Queirós, Sandro; Morais, Pedro; Oliveira, Bruno; Fonseca, Jaime C.; Vilaça, João L.
Highlights: A systematic review of kidney segmentation methods in medical images is presented. A comprehensive description of methods is provided. Methods for ultrasound, magnetic resonance, and computed tomography are reviewed. The methods are divided according to their theoretical approach. The most suitable segmentation method depends on the imaging modality. Abstract: Background and objective: Segmentation is an essential step in computer-aided diagnosis and treatment planning of kidney diseases. In recent years, several researchers proposed multiple techniques to segment the kidney in medical images from distinct imaging acquisition systems, namely ultrasound, magnetic resonance, and computed tomography. This article aims to present a systematic review of the different methodologies developed for kidney segmentation. Methods: With this work, it is intended to analyze and categorize the different kidney segmentation algorithms, establishing a comparison between them and discussing the most appropriate methods for each modality. For that, articles published between 2010 and 2016 were analyzed. The search was performed in Scopus and Web of Science using the expressions "kidney segmentation" and "renal segmentation". Results: A total of 1528 articles were retrieved from the databases, and 95 articles were selected for this review. After analysis of the selected articles, the reviewed segmentation techniques were categorized according to their theoretical approach. Conclusions: Based on the performed analysis, it was possible to identify segmentation approaches based on distinct image processing classes that can be used to accurately segment the kidney in images of different imaging modalities. Nevertheless, further research on kidney segmentation must be conducted to overcome the current drawbacks of the state-of-the-art methods. Moreover, a standardization of the evaluation database and metrics is needed to allow a direct comparison between methods.